Prehistoric Farming Settlements in Western Anatolia: Archaeobotanical Insights into the Late Chalcolithic of the Izmir Region, Turkey - Maltas, Tom; Şahoğlu, Vasif; Erkanal†, Hayat; Tuncel, Rıza (Journal of Mediterranean Archaeology, 2022)
Recovery of archaeobotanical assemblages from Late Chalcolithic Bakla Tepe and Liman Tepe in western Anatolia has provided the opportunity for in-depth analysis of agricultural strategies and the organisation of farming-related activity at the two sites. We find that Late Chalcolithic farmers utilised five major crop taxa, potentially including two mixed crops. The two sites also provide the first evidence for Spanish vetchling and winged vetchling cultivation in prehistoric Anatolia and the earliest evidence for this practice to date anywhere. We suggest that the settlements were organised into small, co-residential households that processed and stored their own crops, but we also propose that potentially communal extra-household storage and high levels of social monitoring may attest to supra-household cooperation. The later agricultural history of the vetchling species and the prevalence of extra-household storage at sites in coastal western Anatolia and the eastern Aegean islands add to evidence for a cultural koine between these regions in the fourth and third millennia bc. We also suggest that the large size of extra-household storage structures and the narrow range of crops cultivated at some Late Chalcolithic sites are consistent with the emergence of more extensive farming systems than those of earlier periods. Evidence for the use of extensive agricultural production to amass arable wealth by the citadel elites of later Early Bronze Age western Anatolia suggests that the agro-ecological foundations for emergent wealth inequality within the region were laid during the Late Chalcolithic. Testing this hypothesis through direct evidence for the nature of Late Chalcolithic farming systems is a key aim of ongoing research.